Florida Rosemary, Ceratiola ericoides - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Florida rosemary is important in maintaining back dune structures and is found inland in scrub communities. This plant is found throughout scrub plant communities in Florida, and more broadly is found west to Mississippi and east to South Carolina in xeric soils and in communities with fire return intervals of 20 to 40 years. Plants are killed by fire and storm surge events, but seeds germinate readily post-disturbance. Its fruit is an important food source for wildlife but is not produced until plants are at least 12 years old. https://edis.ifas.ufl.edu/sg164